PENERAPAN METODE TOPSIS UNTUK PENERIMAAN BANTUAN SOSIAL DISABILITAS PADA DINAS SOSIAL KOTA BENGKULU - Yuliadarnita Yuliadarnita; Renaldi Renaldi; Rozali Toyib; Ardi Wijaya (UNIVED Press, 2024)
So far, the quota of recipients of aid for the deaf is determined directly by the Social Service where this has an ineffective impact, such as there are people who deserve this assistance but cannot get it due to the limited quota of recipients and this also raises community perceptions due to the possibility of being affected by subjectivity in in determining the beneficiaries of assistance, so that it is not uncommon for efforts to distribute this assistance to have the potential to be very large not on target. A decision support system or Decision Support System (DSS) is a system that can assist in making decisions in an organization or company by applying methods that are appropriate to the areas of decision taken. Making decisions manually without the help of a SPK will result in an assessment that is not objective and does not appropriate. The TOPSIS method is a multi-criteria decision-making method by applying a weighted value to each criterion. The conclusion is that the computation is more efficient, the computational calculation is faster, and the decision-making method is faster. haven't made a perfect decision yet.